Polymer waterproof coiled material and preparation method thereof

By using components such as Yanshan Petrochemical IIR-1751 and Xinhui 532 butyl rubber in the self-adhesive layer of polymer waterproof coil, combined with the protective layer of calcium carbonate composite material, the problem of insufficient stickiness of traditional coils is solved, and higher bond stability and service life are achieved.

CN120003101AActive Publication Date: 2025-05-16河北豫源防水材料有限公司
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510384272.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2025-05-16
Estimated Expiration
2045-03-28

AI Technical Summary

Technical Problem

The lack of stickiness of traditional polymer waterproof coils leads to failure of bonding under extreme temperature difference environments and humid conditions, affecting service life and structural safety.

Method used

The self-adhesive layer consisting of two butyl rubbers, SBS, tackifying resins, anti-aging agents, fillers and vulcanizing agents in Yanshan Petrochemical IIR-1751 and Xinhui 532 are used to improve the viscosity of the waterproof coil through synergistic effects, and calcium carbonate composite material is added to the protective layer to enhance the tensile strength.

Benefits of technology

It significantly improves the stickiness of the waterproof coil, extends the service life, reduces the risk of slippage, and maintains bonding stability in extreme environments, enhancing structural safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of waterproof materials, and provides a macromolecular waterproof roll and a preparation method thereof. The macromolecular waterproof coiled material sequentially comprises a protective layer, an asphalt layer, a self-adhesive layer and a diaphragm layer from top to bottom, and the self-adhesive layer is prepared from, by weight, 60-80 parts of butyl rubber, 10-20 parts of SBS, 6-14 parts of tackifying resin, 1-2 parts of anti-aging agent, 15-25 parts of filler and 2-3 parts of vulcanizing agent; the butyl rubber comprises first butyl rubber and second butyl rubber, the model of the first butyl rubber is Yanshan Petrochemical IIR-1751, and the model of the second butyl rubber is Xinxi 532. According to the technical scheme, the problem of low holding power of the high-molecular waterproof coiled material in the prior art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of waterproof materials, and in particular to a polymer waterproof coiled material and a preparation method thereof. Background Art

[0002] As the core material of building waterproofing projects, the performance of polymer waterproofing membranes directly affects the durability and safety of buildings. The mainstream polymer waterproofing membranes on the market include polyvinyl chloride, thermoplastic polyolefins, EPDM rubber and high-density polyethylene. These materials are widely used in roofing, underground projects and water conservancy facilities due to their excellent weather resistance, tensile strength and chemical corrosion resistance. However, long-term engineering practice has shown that the lack of adhesion between the membrane and the base has become a key bottleneck restricting its service life.

[0003] Traditional bonding systems have multiple inherent defects in terms of bonding stability. First, the temperature sensitivity of the self-adhesive layer is significant: at high temperatures, the self-adhesive layer softens, causing the coil to slip; at low temperatures, the self-adhesive layer becomes brittle, causing interfacial cracking. This phenomenon is particularly prominent in areas with extreme temperature differences. For example, under the alternating effects of high temperature and humidity in southern my country and severe cold and dry environments in the north, the problem of coil bonding failure occurs frequently. Secondly, the polarity difference between polymer materials and substrates such as concrete and metal leads to poor interfacial compatibility. For example, the surface energy of EPDM rubber is much lower than that of concrete. The mismatch in polarity leads to insufficient interfacial bonding strength, and the penetration of water molecules in a humid environment further weakens the bonding effect. In addition, ultraviolet radiation, ozone and chemical media will accelerate the breakage of adhesive molecular chains, resulting in a decrease in bonding strength.

[0004] Leakage caused by insufficient adhesion has serious consequences in actual projects. Taking underground utility tunnels as an example, due to long-term groundwater pressure and dynamic loads, traditional rolls are prone to water leakage at the joints due to adhesion failure, which is costly to repair and affects structural safety. In the roofing projects of super high-rise buildings, the combined effects of strong wind loads and temperature changes further amplify the risk of roll slippage.

[0005] As building waterproofing projects develop towards long-term, green and intelligent directions, the industry has put forward higher requirements for material performance. Key projects such as cross-sea bridges and urban subways require materials with higher bonding stability. However, existing technologies are difficult to meet the needs.

[0006] In summary, the problem of insufficient adhesion of traditional polymer waterproof membranes has become a major obstacle to the development of the industry. It is of vital importance to develop a polymer waterproof membrane with improved adhesion. Summary of the invention

[0007] The present invention provides a polymer waterproofing coiled material and a preparation method thereof, which solves the problem of low stickiness of the polymer waterproofing coiled material in the related art.

[0008] The technical solution of the present invention is as follows: The present invention provides a polymer waterproofing coiled material, which comprises a protective layer, an asphalt layer, a self-adhesive layer, and a diaphragm layer in order from top to bottom. The raw materials of the self-adhesive layer comprise the following components by weight: 60-80 parts of butyl rubber, 10-20 parts of SBS, 6-14 parts of tackifying resin, 1-2 parts of antioxidant, 15-25 parts of filler, and 2-3 parts of vulcanizing agent; The butyl rubber includes a first butyl rubber and a second butyl rubber. The first butyl rubber and the second butyl rubber have different models. The model of the first butyl rubber is Yanshan Petrochemical IIR-1751, and the model of the second butyl rubber is Xinhui 532.

[0009] As a further technical solution, the mass ratio of the first butyl rubber to the second butyl rubber is 7-9:2.

[0010] In the present invention, when the mass ratio of Yanshan Petrochemical IIR-1751 butyl rubber to Xinhui 532 butyl rubber is 7-9:2, the adhesion of the waterproof membrane is further improved.

[0011] As a further technical solution, the tackifying resin includes one or two of phenolic resin and rosin resin; The antioxidant includes one or two of antioxidant MB and antioxidant RD; The filler includes one or two of calcium carbonate and kaolin; The vulcanizing agent includes one or more of dicumyl peroxide, di-tert-butyl peroxide, and benzoyl peroxide.

[0012] In the present invention, a tackifying resin is added to the raw material of the self-adhesive layer, and the tackifying resin inhibits the plastic deformation of the waterproof coiled material under long-term use through the intermolecular entanglement effect, thereby maintaining the durable adhesion of the waterproof coiled material; In the present invention, an antioxidant is added to the raw material of the self-adhesive layer, and the antioxidant can capture free radicals generated by rubber oxidation, terminate chain oxidation, and extend the service life of the waterproof coiled material; In the present invention, calcium carbonate or kaolin is added to the raw material of the self-adhesive layer as a filler, and the filler can fill the gap between rubber molecules, thereby achieving the effect of reinforcing and hardening the waterproof coiled material; In the present invention, a vulcanizing agent is added to the raw material of the self-adhesive layer, and the vulcanizing agent enables the rubber to form a three-dimensional network structure, thereby improving the heat resistance of the self-adhesive layer, reducing the relaxation rate of the self-adhesive layer, and maintaining the elasticity of the self-adhesive layer.

[0013] As a further technical solution, the protective layer raw material includes the following components in parts by weight: 70-80 parts of high-density polyethylene, 7-11 parts of nitrile rubber, 16-22 parts of calcium carbonate, 1-2 parts of antioxidant, and 2-3 parts of vulcanizer.

[0014] In the present invention, high-density polyethylene serves as a rigid skeleton of the protective layer, which can help the waterproof coiled material resist stress damage, and the nitrile rubber can promote the uniform dispersion of calcium carbonate in the matrix.

[0015] As a further technical solution, the calcium carbonate is a calcium carbonate composite material; The raw materials of the calcium carbonate composite material include calcium carbonate and m-hydroxycinnamic acid.

[0016] As a further technical solution, the preparation method of the calcium carbonate composite material comprises the following steps: Adding calcium carbonate to a solvent, adding m-hydroxycinnamic acid, stirring until uniform, and drying to obtain a calcium carbonate composite material; During the stirring, the temperature is 60-70°C; The solvent includes one or two of ethanol and isopropanol; The weight volume ratio of the calcium carbonate to the solvent is 1g:2~3mL.

[0017] In the present invention, calcium carbonate is treated with m-hydroxycinnamic acid to obtain a calcium carbonate composite material, polar groups of the calcium carbonate composite materials interact with each other, and the calcium carbonate composite material and polyethylene interact with each other, thereby improving the tensile strength of the protective layer.

[0018] As a further technical solution, the mass ratio of the calcium carbonate to m-hydroxycinnamic acid is 45-55:1.

[0019] In the present invention, the tensile strength of the protective layer is improved by adjusting the mass ratio of calcium carbonate to m-hydroxycinnamic acid to 45-55:1.

[0020] As a further technical solution, in the protective layer raw material, the antioxidant includes one or both of antioxidant 1076 and antioxidant 1010; The vulcanizing agent includes one or more of dicumyl peroxide, di-tert-butyl peroxide, and benzoyl peroxide.

[0021] In the present invention, antioxidants are added to the raw materials of the protective layer, and antioxidants 1076 and 1010 are selected as the antioxidants. When the antioxidants are added, the antioxidant property of the protective layer is improved through the steric stabilization mechanism and the synergistic effect of multiple functional groups.

[0022] As a further technical solution, the material of the asphalt layer includes modified asphalt; The material of the diaphragm layer includes polyethylene.

[0023] The present invention also provides a method for preparing a polymer waterproofing coiled material, which is used to prepare the polymer waterproofing coiled material, comprising the following steps: S1, mixing the raw materials of the self-adhesive layer, and extruding the self-adhesive layer; S2, mixing the raw materials of the protective layer and extruding the protective layer; S3. After compounding in the order of protective layer, asphalt layer, self-adhesive layer and diaphragm layer from top to bottom, a polymer waterproofing membrane is obtained.

[0024] The working principle and beneficial effects of the present invention are: 1. In the present invention, two types of butyl rubbers, namely, Yanshan Petrochemical IIR-1751 and Xinhui 532, are added to the self-adhesive layer. The two types of butyl rubbers work synergistically to improve the adhesion of the waterproof membrane, prevent the occurrence of adhesion failure problems, reduce the slip risk of the polymer waterproof membrane, and extend the service life of the waterproof membrane.

[0025] 2. In the present invention, SBS is added to the self-adhesive layer. As a thermoplastic elastomer, SBS can significantly improve the dynamic mechanical properties of the adhesive, allowing it to maintain flexibility in a low temperature environment and avoid brittle cracking. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] In the following embodiments and comparative examples, the model of SBS is YH-792, the model of phenolic resin is 2402, the model of rosin resin is 138 rosin glycerol ester, the particle size of calcium carbonate is 1000 mesh, the purity is 99wt%, the model of high-density polyethylene is HHM5502LW, the model of nitrile rubber is NBR-1704, the modified asphalt is purchased from Weifang Changxu Building Materials Co., Ltd., the model is CX-CW211, and the model of polyethylene is DFDA-7042.

[0028] Example 1 A polymer waterproofing roll material, which comprises, from top to bottom, a protective layer, an asphalt layer made of modified asphalt, a self-adhesive layer, and a diaphragm layer made of polyethylene, wherein the raw materials of the self-adhesive layer comprise the following components by weight: 80 parts of butyl rubber, 20 parts of SBS, 14 parts of phenolic resin, 2 parts of antioxidant MB, 25 parts of calcium carbonate, and 3 parts of diisopropylbenzene peroxide; The butyl rubber is Yanshan Petrochemical IIR-1751 butyl rubber and Xinhui 532 butyl rubber in a mass ratio of 11:2; The protective layer raw material includes the following components by weight: 80 parts of high-density polyethylene, 11 parts of nitrile rubber, 22 parts of calcium carbonate, 2 parts of antioxidant 1076, and 3 parts of diisopropylbenzene peroxide; The preparation method of the polymer waterproofing coiled material comprises the following steps: S1, mixing the raw materials of the self-adhesive layer, and extruding the self-adhesive layer; S2, mixing the raw materials of the protective layer and extruding the protective layer; S3. After compounding in the order of protective layer, asphalt layer, self-adhesive layer and diaphragm layer from top to bottom, a polymer waterproofing membrane is obtained.

[0029] Example 2 A polymer waterproofing coiled material, comprising, from top to bottom, a protective layer, an asphalt layer made of modified asphalt, a self-adhesive layer, and a diaphragm layer made of polyethylene, wherein the raw materials of the self-adhesive layer include the following components by weight: 60 parts of butyl rubber, 10 parts of SBS, 6 parts of rosin resin, 1 part of antioxidant RD, 15 parts of kaolin, and 2 parts of di-tert-butyl peroxide; The butyl rubber is Yanshan Petrochemical IIR-1751 butyl rubber and Xinhui 532 butyl rubber in a mass ratio of 5:2; The protective layer raw material includes the following components by weight: 70 parts of high-density polyethylene, 7 parts of nitrile rubber, 16 parts of calcium carbonate, 1 part of antioxidant 1076, and 2 parts of di-tert-butyl peroxide; The preparation method of the polymer waterproofing coiled material comprises the following steps: S1, mixing the raw materials of the self-adhesive layer, and extruding the self-adhesive layer; S2, mixing the raw materials of the protective layer and extruding the protective layer; S3. After compounding in the order of protective layer, asphalt layer, self-adhesive layer and diaphragm layer from top to bottom, a polymer waterproofing membrane is obtained.

[0030] Example 3 A polymer waterproofing roll material, which comprises, from top to bottom, a protective layer, an asphalt layer made of modified asphalt, a self-adhesive layer, and a diaphragm layer made of polyethylene, wherein the raw materials of the self-adhesive layer comprise the following components by weight: 70 parts of butyl rubber, 15 parts of SBS, 9 parts of phenolic resin, 1.5 parts of antioxidant MB, 20 parts of calcium carbonate, and 2.5 parts of benzoyl peroxide; The butyl rubber is Yanshan Petrochemical IIR-1751 butyl rubber and Xinhui 532 butyl rubber in a mass ratio of 5:1; The protective layer raw material includes the following components by weight: 75 parts of high-density polyethylene, 9 parts of nitrile rubber, 18 parts of calcium carbonate, 1.5 parts of antioxidant 1076, and 2.5 parts of benzoyl peroxide; The preparation method of the polymer waterproofing coiled material comprises the following steps: S1, mixing the raw materials of the self-adhesive layer, and extruding the self-adhesive layer; S2, mixing the raw materials of the protective layer and extruding the protective layer; S3. After compounding in the order of protective layer, asphalt layer, self-adhesive layer and diaphragm layer from top to bottom, a polymer waterproofing membrane is obtained.

[0031] Example 4 The only difference between this embodiment and embodiment 3 is that the butyl rubber in this embodiment is Yanshan Petrochemical IIR-1751 butyl rubber and Xinhui 532 butyl rubber in a mass ratio of 3:1.

[0032] Example 5 The only difference between this embodiment and embodiment 3 is that the butyl rubber in this embodiment is Yanshan Petrochemical IIR-1751 butyl rubber and Xinhui 532 butyl rubber in a mass ratio of 7:2.

[0033] Example 6 The only difference between this embodiment and embodiment 3 is that the butyl rubber in this embodiment is Yanshan Petrochemical IIR-1751 butyl rubber and Xinhui 532 butyl rubber in a mass ratio of 9:2.

[0034] Example 7 The difference between this embodiment and embodiment 6 is that the raw material of the protective layer in this embodiment includes the following components by weight: 75 parts of high-density polyethylene, 9 parts of nitrile rubber, 18 parts of calcium carbonate composite material, 1.5 parts of antioxidant 1076, and 2.5 parts of benzoyl peroxide; The raw materials of the calcium carbonate composite material include calcium carbonate and m-hydroxycinnamic acid in a mass ratio of 45:1; The preparation method of the calcium carbonate composite material comprises the following steps: Add calcium carbonate to isopropanol, add m-hydroxycinnamic acid, stir at 70°C until uniform, and dry to obtain a calcium carbonate composite material; The weight volume ratio of calcium carbonate to isopropanol is 1 g:2 mL.

[0035] Example 8 The only difference between this embodiment and embodiment 7 is that the raw materials of the calcium carbonate composite material in this embodiment include calcium carbonate and m-hydroxycinnamic acid in a mass ratio of 55:1.

[0036] Example 9 The only difference between this embodiment and embodiment 7 is that in this embodiment, m-hydroxycinnamic acid is replaced by p-methoxycinnamic acid.

[0037] Example 10 The only difference between this embodiment and embodiment 7 is that in this embodiment, m-hydroxycinnamic acid is replaced by mercaptopropyltrimethoxysilane.

[0038] Embodiment 11 The difference between this embodiment and embodiment 7 is that the preparation method of the calcium carbonate composite material in this embodiment comprises the following steps: Add calcium carbonate to ethanol, add m-hydroxycinnamic acid, stir at 60°C until uniform, and dry to obtain a calcium carbonate composite material; The weight volume ratio of calcium carbonate to ethanol is 1 g:3 mL.

[0039] Comparative Example 1 The difference between this comparative example and Example 3 is that the butyl rubber in this comparative example is Yanshan Petrochemical IIR-1751 butyl rubber.

[0040] Comparative Example 2 The only difference between this comparative example and comparative example 1 is that the butyl rubber in this comparative example is Cenhui 532 butyl rubber.

[0041] Comparative Example 3 The only difference between this comparative example and Example 3 is that the butyl rubber in this comparative example is Yanshan Petrochemical IIR-1751 butyl rubber and JSR BUTYL 268 butyl rubber in a mass ratio of 5:1.

[0042] Comparative Example 4 The only difference between this comparative example and Example 3 is that the butyl rubber in this comparative example is BK-1675N butyl rubber and Xinhui 532 butyl rubber in a mass ratio of 5:1.

[0043] Experimental Example 1 The polymer waterproofing membranes prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were tested for their adhesiveness according to the test method specified in GB / T 35467-2017 "Wet-laid waterproofing membranes". The test results are shown in Table 1.

[0044] Table 1 Adhesion test results

[0045] As can be seen from Table 1, the high molecular waterproofing membrane prepared in the present invention has a sustained adhesion of more than 125 minutes. Therefore, the present invention uses two types of butyl rubber, IIR-1751 from Yanshan Petrochemical and 532 from Xinhui, to synergistically improve the sustained adhesion of the waterproofing membrane.

[0046] Experimental Example 2 The protective layer of the polymer waterproofing membrane prepared in Examples 6 to 11 was tested for longitudinal tensile strength according to the determination method in GB / T 328.9-2007 "Test methods for building waterproofing membranes Part 9: Tensile properties of polymer waterproofing membranes". The test results are shown in Table 2.

[0047] Table 2 Tensile strength test results

[0048] As can be seen from Table 2, the tensile strength of the polymer waterproofing membrane protective layer prepared by the present invention reaches more than 30.4 MPa, and the present invention uses m-hydroxycinnamic acid to treat calcium carbonate to obtain a calcium carbonate composite material, thereby improving the tensile strength of the polymer waterproofing membrane protective layer.

[0049] Experimental Example 3 The protective layer of the polymer waterproofing membrane prepared in Examples 1 to 3 was tested for longitudinal elongation according to the determination method in GB / T 328.9-2007 "Test methods for building waterproofing membranes Part 9: Tensile properties of polymer waterproofing membranes". The test results are shown in Table 3.

[0050] Table 3 Longitudinal elongation test results

[0051] It can be seen from Table 3 that the polymer waterproofing membrane in the present invention can meet the actual use requirements.

[0052] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A polymer waterproofing coiled material, characterized in that: The invention comprises a protective layer, an asphalt layer, a self-adhesive layer and a diaphragm layer in order from top to bottom. The raw materials of the self-adhesive layer comprise the following components by weight: 60-80 parts of butyl rubber, 10-20 parts of SBS, 6-14 parts of tackifying resin, 1-2 parts of antioxidant, 15-25 parts of filler and 2-3 parts of vulcanizing agent. The butyl rubber includes a first butyl rubber and a second butyl rubber. The model of the first butyl rubber is Yanshan Petrochemical IIR-1751, and the model of the second butyl rubber is Xinhui 532.

2. A polymer waterproofing coiled material according to claim 1, characterized in that: The mass ratio of the first butyl rubber to the second butyl rubber is 7-9:

2.

3. A polymer waterproofing coiled material according to claim 1, characterized in that: The tackifying resin includes one or two of phenolic resin and rosin resin; The antioxidant includes one or two of antioxidant MB and antioxidant RD; The filler includes one or two of calcium carbonate and kaolin; The vulcanizing agent includes one or more of dicumyl peroxide, di-tert-butyl peroxide, and benzoyl peroxide.

4. A polymer waterproofing coiled material according to claim 1, characterized in that: The protective layer raw material comprises the following components in parts by weight: 70-80 parts of high-density polyethylene, 7-11 parts of nitrile rubber, 16-22 parts of calcium carbonate, 1-2 parts of antioxidant, and 2-3 parts of vulcanizing agent.

5. A polymer waterproofing coiled material according to claim 4, characterized in that: The calcium carbonate is a calcium carbonate composite material; The raw materials of the calcium carbonate composite material include calcium carbonate and m-hydroxycinnamic acid.

6. A polymer waterproofing coiled material according to claim 5, characterized in that: The preparation method of the calcium carbonate composite material comprises the following steps: Adding calcium carbonate to a solvent, adding m-hydroxycinnamic acid, stirring until uniform, and drying to obtain a calcium carbonate composite material; During the stirring, the temperature is 60-70°C; The solvent includes one or two of ethanol and isopropanol; The weight volume ratio of the calcium carbonate to the solvent is 1g:2~3mL.

7. A polymer waterproofing coiled material according to claim 6, characterized in that: The mass ratio of the calcium carbonate to m-hydroxycinnamic acid is 45-55:

1.

8. The polymer waterproofing coiled material according to claim 4, characterized in that: In the protective layer raw material, the antioxidant includes one or both of antioxidant 1076 and antioxidant 1010; The vulcanizing agent includes one or more of dicumyl peroxide, di-tert-butyl peroxide, and benzoyl peroxide.

9. A polymer waterproofing coiled material according to any one of claims 1 to 8, characterized in that: The material of the asphalt layer includes modified asphalt; The material of the diaphragm layer includes polyethylene.

10. A method for preparing a polymer waterproofing coiled material, used for preparing a polymer waterproofing coiled material as claimed in any one of claims 1 to 9, characterized in that: The following steps are involved: S1, mixing the raw materials of the self-adhesive layer, and extruding the self-adhesive layer; S2, mixing the raw materials of the protective layer and extruding the protective layer; S3. After compounding in the order of protective layer, asphalt layer, self-adhesive layer and diaphragm layer from top to bottom, a polymer waterproofing membrane is obtained.

Citation Information

Patent Citations

  • Peroxide curable butyl rubber compound

    CA2578586A1

  • Protein-modified rubber

    CN104130466A

  • Macromolecular self-adhesive waterproof coiled material and preparation method thereof

    CN118325502A

  • Plastic packaging bottle with good pressure resistance and preparation method thereof

    CN119331333A

  • Multi-layer self-protection self-adhesion waterproof coiled material and preparation method thereof

    CN119614091A